Integration between Lean Production and sustainable value chain in light of the trend towards a sustainable circular economy (Journal of Accounting and Financial Studies ( JAFS ), 2021)
In a resource-limited world, there is an urgent need to develop new economic models, from the traditional unsustainable industrial model of product consumption and disposal, to a new model based on the concepts of sustainability in its comprehensive sense, the so-called circular economy, using fewer resources in manufacturing processes and changing practices in product disposal to waste, by removing its use, recycling and manufacturing to start another manufacturing process. In an era of intense competition in domestic and global markets, the importance of the circular economy is highlighted in its ability to strengthen the competitiveness of enterprises in those markets, by reducing the cost and increasing the quality of the product, whether it is a commodity or a service on the one hand, Social and environmental considerations are taken into account during the production process by producing an environmentally friendly product on the other hand, which has a positive impact on the financial and non-financial performance of these enterprises. The role of the waste-free production system is highlighted in achieving a large part of cost management objectives by focusing on cost reduction and quality improvement based on a range of tools that work effectively in a waste-free production environment, to fulfill customers' wishes by excluding activities that do not add value to the product.A new system has recently emerged, which is complementary to the waste-free production system, which focuses on reducing waste and disadvantage on the one hand, and preserving the environment from pollution, gases and emissions on the other, which is a system of accounting for the costs of the flow of materials, where its role and significant contribution to reducing the volume of waste and gases and reducing losses has emerged, reflecting on costs by reducing them and on the environment, human health and society with positive effects and from this point of view has been geared towards the use of the sustainable value chain that contributes to help the management of the economic unit in the manufacture of environmentally friendly products by correcting the main activities necessary to manufacture the product towards environmental requirements, controls and standards and achieving optimal exploitation of energy, natural resources and raw materials, recycling production residues and moving from traditional production, loss-free production, to enhance the value of the economic unit and add value to the customer.